THE MORPHOLOGICAL PROCESSES OF BUGIS LANGUAGE (A MORPHOLOGICAL STUDY OF BUGIS LANGUAGE THROUGH LATOA SCRIPT) - Usman Nurhayati; Nurkholik Nurkholik (Institut Agama Islam Negeri Palopo, 2018)
This research aims to discuss the morphological process of Bugis language during the period of the seventh king of Bone kingdom. Data of this research is a work of literature from Bone kingdom titled Latoa. This research is descriptive qualitative involving the word-structure rules which attempt to analyze words presented in Latoa. The results show that there are some features marking morphological processes of Bugis language in the sixteenth century. The morphological processes consist of reduplication and affixation. processes of reduplication of Bugis' language are divided into two patterns, those are the reduplication of entire stem and affixing reduplication. Where affixation of Bugis language expresses derivational meanings and inflectional values; the forms of prefixes that are derived from derivational processes are to-, ri- whereas the form of suffixes derived from derivational processes are i, -e, -reng, and na and the form of suffixes expressing inflectional values is na.